Development of fly ash boards with thermal, acoustic and fire insulation properties. (December 2015) - Leiva, C.; Arenas, C.; Vilches, L.F.; Alonso-Fariñas, B.; Rodriguez-Galán, M.
Highlights: Development of a product with good sound absorption properties. Low thermal conductivity at ambient temperatures. High fire resistance. Composed mainly by ashes. Without any leaching impact. Abstract: This paper presents an experimental analysis on a new board composed of gypsum and fly ashes from coal combustion, which are mutually compatible. Physical and mechanical properties, sound absorption coefficient, thermal properties and leaching test have been obtained. The mechanical properties showed similar values to other commercial products. As far as the acoustic insulation characteristics are concerned, sound absorption coefficients of 0.3 and 0.8 were found. The board presents a low thermal conductivity and a fire resistance higher than 50 min (for 4 cm of thickness). The leaching of trace elements was below the leaching limit values. These boards can be considered as suitable to be used in building applications as partitions.